KEBERHASILAN MENGEMBANGKAN USAHA MIKRO (Studi Kasus Buah-buahan Ibu Wartini) - Ledia Santika; Rizkan Rizkan; Ririn Gusti (Jurnal Pendidikan Sepanjang Hayat, 2020)
The fruit business of Mrs. Wartini is is a micro business different from the fruit business in general, because in addition to selling fruits, there are many other sales variations of processed fruits. Thus, the selling differences based on Mrs. Wartini's fruit business are what make researchers interested in conduct research. The purpose of this study is first, to describe the characteristics of success in developing micro-businesses which include orientation to achievement, courage to take risks, hard work, responsibility, commitment and develop and maintain good relations. The research method used in this research is descriptive qualitative method. The results obtained are as follows: first, the aspect of orientation on achievement is the quality of fresh products, many variations of sales and affordable prices. Second, the aspect of courage to take risks is to open a business and dare to stock a lot of fruits. Third, the aspect of hard work, which is employees who arrive early. Fourth, the aspect of responsibility that is paying employees' salaries and fruit suppliers is always on time. Fifth, the aspect of commitment is to the time and tengga issued and always provide immediate fruit. Sixth, aspects of developing and maintaining good relations, namely the existence of a good relationship between the owner and employees, customers and fruit suppliers. Keywords: Success, Business, Micro